Business Process Model Variations in Islamic Boarding Schools Using Requirements Analysis Method - Nuriyanti, Fitri; Izzah, Iffatul; Azizah, Munajatul; Yaqin, Muhammad Ainul (Proceeding International Conference on Science and Engineering, 2020)
The business process at a boarding school is a collection of all the detailed activities that have been arranged in such a way as to solve the existing problems so that the objectives set can be met. There are development standards that can be used as a reference to build architecture and business process models at a boarding school. Every business process has planned many ways to be able to obtain goals precisely. Therefore variations are formed in the business process models. Business process models of variations are a collection of business process models that have the same goals in different ways. Variations in the business process models are needed to achieve the right goals in a variety of ways according to existing resources and needs. From all reviews of the variations, it is necessary to have a cyclomatic complexity to find out how complex the business process models is and to maintain the simplicity of the business process models. This study uses the requirements analysis method, which is the intensive interaction stage between the system analyst and the system user community (end-user), where the system development team shows its expertise to get user feedback and confidence so that it gets good participation. The results of this study are a collection of variations of business process models that have a level of complexity not much different from one variation, with another on each standard applied.